Vertebrate endocrinology. - Norris, David O.; Carr, James A. (Academic Press, an imprint of Elsevier, 2021)
Vertebrate Endocrinology, Sixth Edition, provides a comprehensive, up-to-date treatment of the endocrine system for college and university students as well as researchers. This book is logically arranged, easily comprehended, and well-illustrated. It covers traditional hormone-based systems and introduces all forms of chemical communication, their implications for the health of humans, domesticated, and wild vertebrates. Written by two experts who have completed extensive research in comparative vertebrate endocrinology with an emphasis on natural and anthropogenic environmental factors influencing endocrine systems. Collectively, the authors have taught courses in endocrinology at the undergraduate and graduate level for more than 60 years. After first publishing in 1985, Vertebrate Endocrinology, Sixth Edition, continues to serve as an important resource for graduate students and advanced undergraduates in the biological sciences, animal sciences, and veterinary sciences. Endocrine researchers will also benefit from the book's relevance in the areas of comparative, veterinary, and mammalian endocrinology.